Identification of Gene Variations Associated with Diabetic Neuropathy Using Bioinformatics Approach - Siti Fatimah Sultan; Adisti Putri Novriyanti; Siti Rohmah; Lalu Muhammad Irham; Nanik Sulistyani; Muhammad Ma'ruf (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Diabetic neuropathy is the most common complication of diabetes, experienced by almost 90% of diabetic patients. Pain is one of the most common symptoms of diabetic neuropathy, but the pathophysiologic mechanism of pain is not clearly known. The hypothesis of hyperglycemia toxicity to the development of pain complications has been widely accepted worldwide, but there are still other hypotheses proposed. The basic concept in the management of painful diabetic neuropathy is to exclude other causes of peripheral neuropathic pain, improve glycemic control for prophylactic therapy, and use drugs to reduce pain. Variation data for diabetic neuropathy can be obtained from the Ensembl Genome Browser. Here, genes associated with 26 variants were selected according to Haploreg version 4.2. In addition, protein expression of missense gene variants was examined using the GTEx portal to determine two variants: rs55703767, which encodes the COL4A3 gene, and rs141560952, which encodes the DIS3L2 gene. According to data obtained from the Ensembl Genome Browser, the two most prevalent populations for SNP rs55703767, which is linked to the COL4A3 gene, are in Africa, while SNP rs141560952, which is linked to the DIS3L2 gene, is most prevalent in Africa, the Americas, East Asia, Europe, and South Asia.